WAYANG SANTRI SEBAGAI MODEL DAKWAH ISLAM BERBASIS KEARIFAN LOKAL - Abdul Sofyan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2019)
This study aims to describe and analyze the model of Islamic da’wah based on local wisdom contained in wayang santri performances. The model of Islamic da’wah is a pattern or approach used in broadcasting Islamic values. Wayang santri is a concept of puppet performances specifically used for the purpose of da'wah. This study uses a qualitative research method with a descriptive approach that describes a model of Islamic da'wah with the resource persons of wayang santri, that include dalang, sinden and music players of wayang santri. This research produced several important points regarding the model of Islamic da’wah based on local wisdom in wayang santri, namely regarding the origin and history of the development of wayang santri, the beauty side contained in wayang santri performances, and Islamic values contained in wayang santri performances